PLURALITAS HUKUM KEWARISAN DI INDONESIA : SEBUAH TINJAUAN NORMATIF - Rahmatillah, Nor Annisa (Mitsaqan Ghalizan, 2024)
The purpose of this study is to look at the plurality of inheritance laws in Indonesia from a normative point of view. This research analyzes legislation, legal theory, and inheritance practices in customary law, Islamic law, and positive law. Indonesia is a country with a diverse population in terms of religion and ethics, and has a plural legal system, especially in terms of inheritance. This research uses a normative approach to study the legal provisions governing inheritance. These provisions are found in the Civil Code (KUHPerdata), Islamic law through the Compilation of Islamic Law (KHI), and customs that apply in various regions in Indonesia. This research shows that inheritance law is increasingly visible in its diversity, because in fact the customary inheritance law that applies is not only one, but various following the form of society and the family system of Indonesian society. So that the inheritance law applied to all Indonesian people is still different considering the classifications of citizens. Until now, there is no national inheritance law that can regulate inheritance nationally, so that people in Indonesia can choose between the three inheritance laws.